Permanent record [compact disc, unabridged] - Snowden, Edward J., 1983- (Macmillan Audio, 2019)
"Edward Snowden, the man who risked everything to expose the US government's system of mass surveillance, reveals for the first time the story of his life, including how he helped to build that system and what motivated him to try to bring it down"--Publisher.